2021
DOI: 10.34101/actaagrar/1/9047
|View full text |Cite
|
Sign up to set email alerts
|

A review on the trend of livestock breeds in Laos

Abstract: When the livestock sector is considered an essential role in farmers' livelihood, and local breeds are still the critical component of animal breeding in Laos. Thus, there is a need to review the previous, current situation and prospects for Laos' livestock production. It aimed to study the different traits among the existing dominant local and improved livestock breeds (cattle, pig, and goat) and a more in-depth study on the livestock sector's previous evolving and prospects. Our findings revealed that the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This lack of response regarding questions of ante-mortem health is concerning, as the presence of the ASF outbreak during the study suggests that at least some pigs entering the abattoirs must have been either pre-clinical or clinically affected, but is in line with previous work that identified a lack of appropriate ante-and post-mortem inspection in Lao slaughterhouses [26]. The DLF data presented in Xayalath et al [27] suggested that commercial pigs only made up 9% of the total pig population in Lao PDR in 2019, yet they represented 66% of the study population and as such were a biased subset of Lao pigs. Approximately a quarter of the animals travelled across province borders to be slaughtered in this study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This lack of response regarding questions of ante-mortem health is concerning, as the presence of the ASF outbreak during the study suggests that at least some pigs entering the abattoirs must have been either pre-clinical or clinically affected, but is in line with previous work that identified a lack of appropriate ante-and post-mortem inspection in Lao slaughterhouses [26]. The DLF data presented in Xayalath et al [27] suggested that commercial pigs only made up 9% of the total pig population in Lao PDR in 2019, yet they represented 66% of the study population and as such were a biased subset of Lao pigs. Approximately a quarter of the animals travelled across province borders to be slaughtered in this study.…”
Section: Discussionsupporting
confidence: 83%
“…The DLF data presented in Xayalath et al . [ 27 ] suggested that commercial pigs only made up 9% of the total pig population in Lao PDR in 2019, yet they represented 66% of the study population and as such were a biased subset of Lao pigs. Approximately a quarter of the animals travelled across province borders to be slaughtered in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Others include increased contact with animals due to expansion in livestock farming. Livestock farming in Laos PDR is still largely traditional, with more of small-scale (backyard) local production system 58 , 59 . This farming system promotes more animal contact and the adverse effects associated with livestock farming that may serve as risk factors for HEV infection.…”
Section: Discussionmentioning
confidence: 99%